INSTITUTIONAL REFORMS, INTEREST RATE POLICY AND THE FINANCING OF THE AGRICULTURAL SECTOR IN NIGERIA - Kolawole, Bashir Olayinka (European Scientific Journal, ESJ, 2013)
This study empirically investigates the impact of interest rates and some macroeconomic variables on agricultural performance in Nigeria by employing co-integration and an error correction mechanism (ECM) technique with annual time series data covering the period 1980 to 2011. The results reveal that there is a negative relationship between agricultural value added, interest rate spread, and inflation in the country. By implication, the study deduces that the higher the level of inflation and interest rate spread in the country, the lower the level of